Penerapan Etika Bisnis Islam Terhadap Loyalitas Anggota (Studi Kasus KSPPS BMT Sri Sejahtera Jawa Timur) - Nur Jihan Ainul Arifah; Arasy Fahrullah (Journal of Innovative and Creativity, 2025)
The aim of this research is to find out how the application of Islamic Business Ethics and its impact on consumer loyalty or who in this case is called a member of the KSPPS BMT Sri Sejahtera Java East. This research uses qualitative methods. The purpose of the use of qualitative methods is to know what phenomena are experienced by the subject in the research, in the subject studied there are several types of data, internal and external, the internal subject is the manager of KSPPS BMT Sri Sejahtera Java East, also the officials who are in the Team Goodwill Member Visitation (TGMV) who are tasked with carrying out more activities in the field to meet the members or candidate members of the KSPPS BMT Sri Sejahtera East Java, while the external research subject is a member who has done various academies repeatedly in KSPPS BMT Sri Sajahtera East Java to give information about how to Apply Islamic Business Ethics in the KSPPS BMT Sri Sejahtera East Java. Data collection on this research using interview techniques to find out and obtain the desired data and further with documentation techniques as well as observation in person. The results of this study show that the application of Islamic Business Ethics has a significant impact on the increased loyalty of members of KSPPS BMT Sri Sejahtera East Java, such as the satisfaction of members through the performance of honest employees and paying attention for the comfort of both sides.